Doing education policy enactment research in a minor key. Issue 2 (4th March 2017) - Heimans, Stephen; Singh, Parlo; Glasswell, Kathryn
ABSTRACT: This article discusses 'minor key research' and doing this kind of research as 'response-ability'. We explore the possibilities that education policy enactment research might hold for theorising and doing research, not just for work on 'how schools do policy', but also for how researchers do policy research with schools. A methodological question is raised here by us with respect to what researchers might 'do' in schools and other policy locations (such as when working with bureaucrats or politicians). We also discuss our researcher responsibility with respect to such work, and we have attempted to respond to the questions: 'Is there an alternative for the current regime of accountability? Are there ways to resist and intervene in the current culture of accountability?' In the first section, we focus on minor key research, and in the second section we discuss doing minor key research as 'response-ability'.